The Kaplan–Meier theatre. (2nd February 2016) - Gerds, Thomas A.
Summary: Survival is difficult to estimate when observation periods of individuals differ in length. Students imagine sailing the Titanic and then recording whether they "live" or "die". A clever algorithm is performed which results in the Kaplan‐Meier estimate of survival.